Directional Fluid Transport across Organ–Blood Barriers: Physiology and Cell Biology - Caceres, Paulo S. (Cold Spring Harb Perspect Biol, 2017)
Directional fluid flow is an essential process for embryo development as well as for organ and organism homeostasis. Here, we review the diverse structure of various organ–blood barriers, the driving forces, transporters, and polarity mechanisms that regulate fluid transport across them, focusing on kidney–, eye–, and brain–blood barriers. We end by discussing how cross talk between barrier epithelial and endothelial cells, perivascular cells, and basement membrane signaling contribute to generate and maintain organ–blood barriers.